Periodontal Health Status and Treatment Needs of Visually Impaired Student Attending “Extraordinary School in Jember Regency - Ni Luh Putu Diah Laksmi Dewi; Roedy Budirahardjo; Sulistiyani Sulistiyani (Humanistic Network for Science and Technology (HNST), 2020)
Visually impaired people usually have limitation to do their activities in maintaining oral health including the periodontal tissue. This condition leads to inadequate efforts to maintain oral health that can cause various diseases, one of which is periodontal disease. Periodontal disease will gradually develop become severe, and therefore it is necessary to take proper care in handling it. The aim of this study was to determine the periodontal health status and the level of periodontal disease care needs of blind students in SLB Jember Regency. This research was a descriptive observational study with a cross sectional approach. The research sample of 20 people were obtained using the total sampling method. The health status of the periodontal tissue and the need for treatment are examined using CPITN. Subsequent research data are grouped and distributed based on gender and age. The result showed that the most common periodontal tissue health status was score two with clinical features of subgingival calculus or supragingival calculus with a total of 50%, while the most needed treatment needs were improvement in oral hygiene accompanied by 85% professional scaling. Keywords: periodontal health status; periodontal treatment needs; CPITN; visually impaired